WEBSITE APPLICATIONS FOR LEARNING JAPANESE SCHOOL CHILDREN BASIC USING MACROMEDIA DREAMWEAVER. - Reza Kautsar; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2007)
Internet is now become a choice of the most effective indisseminating information, because the Internet has the reach of the network very wide. One of the great information that gets a place on the Internet, among others, information relating to education, especially the Japanese language education. This information is conveyed through one information storage medium on the Internet is the Web site.Japanese language is  the language of the world. In all areas, especially in the field  information technology, all using the Japanese language. Japanese language should be introduced at an early age, so that future generations of children to become an outstanding successor.Scientific writing is trying to explain how making aWeb site about learning Japanese. Starting from design stage to design a Web site ready to be published on the Internet. All are made withusing Macromedia Dreamweaver MX software.